Measures for enhancing auditor independence: perceptions of spanish non-professional investors and auditors - Quick, Reiner; Sánchez-Toledano, Daniel David; Sánchez-Toledano, Joaquín Ignacio (Elsevier, 2024)
Auditors fulfill a crucial societal role by increasing the credibility of financial reports, which requires that appropriate audit quality be provided and auditors are factually independent and perceived as such. So far, regulators and researchers have focused on a few measures for improving independence, namely the prohibition of non-audit services (NAS), audit firm and audit partner rotation, and joint audits. Despite these regulatory initiatives, accounting scandals still happen, and the independence of the auditors involved is questioned. Therefore, this explorative study aims to identify alternative measures that may strengthen auditor independence. Non-professional investors and auditors participated in a survey to identify promising independence-enhancing measures. Surprisingly, not only non-professional investors but also auditors support the implementation of many instruments. Non-professional investors rate measures related to oversight, controls, and sanctions as particularly useful. Likewise, auditors perceive measures for oversight and control as helpful but rank most sanctions lower than non-professional investors. They also support a stricter civil liability and rank some direct independence-improving measures as highly useful. Overall, the participants perceive a greater need for improving the independence of public interest entity (PIE) auditors. This explorative study widens the research horizon by adding alternative measures for improving independence in appearance. Thus, researchers may identify promising avenues for future research. Also, the paper is of interest to regulators and potentially helps in setting independence standards. Auditors and audit committees can identify opportunities for taking voluntary actions to ensure factual and perceived auditor independence.
Keywords: Auditoría; Empresas auditoras; Responsabilidad social de la empresa; Ética empresarial; Auditor independence; Audit quality; Independence perceptions; Survey